Sistem Informasi Administrasi Berkas Pengukuran di Badan Pertanahan Nasional Kota Langsa - Tri Novriza Putri Halimahtun Sakdiah; Nurul Fadillah (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
The need for land is currently increasing in line with the increase in population and other needs related to land. In handling the incoming letter, the process mechanism for making land certificates starts from the applicant who has to complete the requirements and goes through a very long process such as the Measurement process which causes frequent piling of files in the Measurement section. Therefore, I want to create a measurement information system that can log files in a structured manner, know the position of the files in each subprocess and can display the time when employees provide or input reports when they are finished in their duties. The purpose of this system is to view incoming files in accordance with their respective subsections with computerized and structural versions. In this section of Measurement, there are 9 processes including Admin I - Measurement - Admin II - Printing - Plot Check - Head of Sub-Section - Head of Section - Admin III. With this Measurement Information System, it can minimize the occurrence of file loss in any subsection, because with this system the data that is inputted is stored safely and there is a data history menu where we can see where the file has been.